Chemical Doping Effects on CVD‐Grown Multilayer MoSe2 Transistor. (14th April 2018) - Yoo, Hocheon; Hong, Seongin; Moon, Hyunseong; On, Sungmin; Ahn, Hyungju; Lee, Han‐Koo; Kim, Sunkook; Hong, Young Ki; Kim, Jae‐Joon
Abstract: Multilayer transition metal dichalcogenides (TMDs) potentially provide opportunities for large‐area electronics, including flexible displays and wearable sensors. However, most TMDs suffer from a Schottky barrier (SB) and nonuniform defects, which severely limit their electrical performances. Here, a novel chemical doping scheme is presented using poly‐(diketopyrrolopyrrole‐terthiophene) (PDPP3T) to compensate the defects and SB of multilayer molybdenum diselenide (MoSe2 ), exhibiting greatly enhanced electrical characteristics, including on‐current (≈2000‐fold higher) and photoresponsivity (≈10‐fold larger) over the baseline MoSe2 device. Based on comprehensive analysis using X‐ray photoelectron spectroscopy, grazing incidence wide‐angle X‐ray diffraction, atomic force microscopy, and near‐edge X‐ray absorption of fine structure, it is shown that two mechanisms (dipole‐induced and charge‐transfer doping effects) account for such enhancements in the multilayer MoSe2 device. The methodical generality of the strong n‐doping behavior of multilayer MoSe2 is further demonstrated by applying thiophene instead of PDPP3T. Abstract : A doping technique for chemical vapor deposition grown multilayer MoSe2 thin‐film transistors using spin coating of poly‐(diketopyrrolopyrrole‐terthiophene) is presented, which produces a strong n‐type multilayer molybdenum diselenide. Extensive analysis using 2D grazing incidence wide‐angle X‐ray diffraction, X‐ray photoelectron spectroscopy, and near‐edge X‐ray absorption of fine structure suggests that dipole‐induced effects and charge transfer account for the n‐doping phenomena.